1999
DOI: 10.1007/s001340051030
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin: a new serum marker of myocardial injury in sepsis

Abstract: Identification of myocardial dysfunction in septic patients has been a challenging task. Troponin I, a serum marker of myocardial injury, may be of great help in the recognition of myocardial involvement by sepsis in a noninvasive and readily available way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(103 citation statements)
references
References 10 publications
3
94
2
4
Order By: Relevance
“…Both AKI and myocardial dysfunction are also common in sepsis. [70][71][72] Data have found that 30-80% of septic patients have elevated cardiac-specific troponins [73][74][75] Hepato-Renal syndrome…”
Section: Secondary Cardio-renal Syndromes (Type 5 Crs)mentioning
confidence: 99%
“…Both AKI and myocardial dysfunction are also common in sepsis. [70][71][72] Data have found that 30-80% of septic patients have elevated cardiac-specific troponins [73][74][75] Hepato-Renal syndrome…”
Section: Secondary Cardio-renal Syndromes (Type 5 Crs)mentioning
confidence: 99%
“…The mortality from septic shock syndrome ranges from 20% to 90%, depending upon the patient's age and associated pathologies (Wenzel and Edmond, 2001). Using clinical markers for myocardial damage such as cardiac troponin I (cTnI), various research laboratories have suggested that almost 50% of septic patients exhibit myocardial dysfunction in ICUs (Charpentier et al, 2004;Fernandes et al, 1999;Maeder et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…12 Of note, multivessel coronary artery disease was more prevalent across progressively higher quartiles of troponin T, suggesting an ischemic mechanism for the troponin increase in this patient population. 13 In heart failure patients, elevated troponin is associated with the risk of death and rehospitalization regardless of underlying cause and the three-year survival is about 29%. 14,15 Critically ill patients who require stay in an intensive care unit are a heterogeneous group of patients who are ill for a variety of heterogeneous diseases.…”
Section: Discussionmentioning
confidence: 99%